Atypical Psoriatic Arthritis: A Case Report - Yasemin Turan; Ömer Faruk Şendur; Işıl Karataş-Berkit; Ayşe Ünübol (Archives of Rheumatology, 2009)
Psoriatic arthritis (PsA) is chronic inflammatory rheumatic disease characterized by of peripheral arthritis, enthesitis, spondylitis and psoriasis. The mean age at onset of PsA is in the range of 30-50 years. In clinically, approximately 17% of patients develop arthritis before the onset of psoriasis. Osgood Schlatter syndrome presents in growing children (boys, 12-15 years; girls, 8-12 years) with local pain, swelling and tenderness over the tibial tuberosity. In this paper, Osgood Schlatter syndrome causing bilateral knee pain during the fallow-up of a patient with atypical PsA is reported. (Turk J Rheumatol 2009; 24: 225-7)